Unconventional Protein Secretion Dependent on Two Extracellular Vesicles: Exosomes and Ectosomes - Meldolesi, Jacopo (Frontiers in Cell and Developmental Biology, 2022)
In addition to conventional protein secretion, dependent on the specific cleavage of signal sequences, proteins are secreted by other processes, all together called unconventional. Among the mechanisms operative in unconventional secretion, some are based on two families of extracellular vesicle (EVs), expressed by all types of cells: the exosomes (before secretion called ILVs) and ectosomes (average diameters ∼70 and ∼250 nm). The two types of EVs have been largely characterized by extensive studies. ILVs are assembled within endocytic vacuoles by inward budding of small membrane microdomains associated to cytosolic cargos including unconventional secretory proteins. The vacuoles containing ILVs are called multivesicular bodies (MVBs). Upon their possible molecular exchange with autophagosomes, MVBs undergo two alternative forms of fusion: 1. with lysosomes, followed by large digestion of their cargo molecules; and 2. with plasma membrane (called exocytosis), followed by extracellular diffusion of exosomes. The vesicles of the other type, the ectosomes, are differently assembled. Distinct plasma membrane rafts undergo rapid outward budding accompanied by accumulation of cytosolic/secretory cargo molecules, up to their sewing and pinching off. Both types of EV, released to the extracellular fluid in their complete forms including both membrane and cargo, start navigation for various times and distances, until their fusion with target cells. Release/navigation/fusion of EVs establish continuous tridimensional networks exchanging molecules, signals and information among cells. The proteins unconventionally secreted via EVs are a few hundreds. Some of them are functionally relevant (examples FADD, TNF, TACE), governing physiological processes and important diseases. Such proteins, at present intensely investigated, predict future discoveries and innovative developments, relevant for basic research and clinical practice.